2011
DOI: 10.1038/onc.2010.611
|View full text |Cite
|
Sign up to set email alerts
|

Activation of nuclear factor-kappa B signalling promotes cellular senescence

Abstract: Cellular senescence is a program of irreversible cell cycle arrest that normal cells undergo in response to progressive shortening of telomeres, changes in telomeric structure, oncogene activation or oxidative stress. The underlying signalling pathways, of major clinicopathological relevance, are unknown. We combined genome-wide expression profiling with genetic complementation to identify genes that are differentially expressed when conditionally immortalised human fibroblasts undergo senescence upon activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
162
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(173 citation statements)
references
References 54 publications
(69 reference statements)
8
162
2
1
Order By: Relevance
“…IL1-a is a potent inducer of the NFkB pathway, which together with C/EBPb, is critical for synthesis of the SASP factors. 17,[20][21][22][23][24] We confirmed such a role of NFkB in our system by silencing either IKKa or IKKb and measuring IL-6 and KC levels (Figure 4d). Whereas silencing of IKKa had only a modest influence on cytokine secretion, the effect of knocking down IKKb was more profound, as expected for a role of the canonical NFkB pathway on cytokine synthesis.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…IL1-a is a potent inducer of the NFkB pathway, which together with C/EBPb, is critical for synthesis of the SASP factors. 17,[20][21][22][23][24] We confirmed such a role of NFkB in our system by silencing either IKKa or IKKb and measuring IL-6 and KC levels (Figure 4d). Whereas silencing of IKKa had only a modest influence on cytokine secretion, the effect of knocking down IKKb was more profound, as expected for a role of the canonical NFkB pathway on cytokine synthesis.…”
Section: Resultssupporting
confidence: 72%
“…[40][41][42] It should be noted that the thyroid gland is considered to be a dormant, non-regenerative organ with very slow cellular turnover: in humans, it has been estimated that follicular cells divide approximately five times during adult life. 43 A growing number of evidence links activation of the NFkB pathway to induction of the SASP and cellular senescence, 24,44,45 and indeed ChIP experiments demonstrate that p65 is the most abundant transcription factor bound to senescent chromatin. 22 As for the mechanism by which Spry1 modulates the NFkB pathway, the lack of a universal mode of action of Spry proteins makes it difficult to explore candidate Owing to the absence of true conserved domains in Spry proteins, one strategy to investigate its mechanism of action has been to identify their binding partners, in a 'guiltyby-association' approach.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that inhibition of the DNA damage-responsive kinases ATM and Chk2 prevents the release of some SASP components, whereas p53 obviously restrains SASP formation (Rodier et al, 2009). Important transcriptional activators of the SASP are nuclear factor kappaB (NFkB) and CCAAT/enhancer-binding protein (C/ EBPb) as well as p38 kinase, which appears to be required for sustained NFkB activation (Kuilman et al, 2008;Rovillain et al, 2011;Chien et al, 2011;Jing et al, 2011;Freund et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Many of the SASP factors are bona fide NF-kB targets with NF-kB-binding sites in their promoters (Feuerhake et al 2005;Acosta et al 2008;Kuilman et al 2008), rendering them responsive to NF-kB activation, as shown for poly(ADP-ribose)-polymerase-1 (PARP-1)-mediated genotoxic therapies or induction of oncogenic Ras (Finco et al 1997;Stilmann et al 2009;Ohanna et al 2011). Silencing of NF-kB transcription factors in senescent human fibroblasts enhanced their proliferative capacity, suggesting that NF-kB signaling may indeed contribute to the senescent growth arrest (Rovillain et al 2011).…”
mentioning
confidence: 98%